POLITENESS STRATEGIES USED BY JO AND AMY MARCH ON LITTLE WOMEN - Mayyada; Elisa Nurul Laili (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2021)
This study aims to determine the identity captured from the politeness strategies used by Jo and Amy March on Little Women movie. To analyze the description of politeness strategies used by Jo and Amy March as the main characters in the film, the researcher used the theory of Leech on maxim politeness. Then, this study is using a qualitative descriptive method. Based on the results that have found from Jo and Amy March’s dialogue, they are dominant using agreement maxim because of a close relationship between their family, and also they have close relation and intensiveness with their sisters.